2020
DOI: 10.1038/s41408-020-0298-1
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib-based consolidation or maintenance therapy for multiple myeloma: a meta-analysis

Abstract: Bortezomib-based regimens are widely used as induction therapy for multiple myeloma (MM). Unlike lenalidomide, the role of bortezomib in consolidation and maintenance therapy for MM is less clear. We performed a meta-analysis to evaluate the impact of bortezomib-based consolidation and maintenance therapy on survival outcomes and adverse events. PubMed, Web of Science, Embase databases, and major conference proceedings were searched for randomized controlled trials (RCTs) of bortezomib-based regimens as consol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…The consensus of the Mayo Clinic recommends: immunomodulators maintenance for patients with standard-risk cytogenetics and PI maintenance therapy for patients with high-risk cytogenetics ( 16 ). Data from our center revealed that compared with thalidomide and lenalidomide, PFS and OS can both benefit from bortezomib-based regimens (median PFS: 43.7 vs 38.5 months; median OS: not reached vs 78.5 months), findings consistent with the reported literature ( 18 ). It is worth noting that in the phase III HOVON-65/GMMG-HD4 trial, the early research report showed that OS was superior after bortezomib-based regimens for induction and maintenance compared to non–bortezomib-based regimen inductions and thalidomide maintenance therapy ( 19 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The consensus of the Mayo Clinic recommends: immunomodulators maintenance for patients with standard-risk cytogenetics and PI maintenance therapy for patients with high-risk cytogenetics ( 16 ). Data from our center revealed that compared with thalidomide and lenalidomide, PFS and OS can both benefit from bortezomib-based regimens (median PFS: 43.7 vs 38.5 months; median OS: not reached vs 78.5 months), findings consistent with the reported literature ( 18 ). It is worth noting that in the phase III HOVON-65/GMMG-HD4 trial, the early research report showed that OS was superior after bortezomib-based regimens for induction and maintenance compared to non–bortezomib-based regimen inductions and thalidomide maintenance therapy ( 19 ).…”
Section: Discussionsupporting
confidence: 90%
“…Clinic`al trial data have shown that bortezomib consolidation after ASCT only improved the PFS of patients not achieving at least VGPR, had no effect on patients who achieved at least VGPR, and did not prolong OS in both categories of patients ( 23 ). Consolidation therapy refers to the utilization of a short course of treatment to reduce the number of residual tumor cells, which can prolong PFS but not OS ( 18 ). Consolidation and maintenance therapy play a different role in patients’ outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As the consensus of Mayo Clinic recommends: immunomodulators maintenance is recommended for patients with standard-risk cytogenetics, meanwhile, PI maintenance for high-risk cytogenetics [16]. Data from our center revealed that compared with thalidomide and lenalidomide, the PFS and OS can both bene t from bortezomib-based regimens (median PFS: 43.7 vs. 38.5 months; median OS: not reached vs. 78.5 months), which was consistent with the literature [18]. It is worth noting that in the phase III HOVON-65/GMMG-HD4 trial the early research report showed the OS was superior in bortezomib-based regimens induction and maintenance arm to non-bortezomib-based regimens induction and thalidomide maintenance arm [19], however, after long-term follow-up, the OS was no difference between two arms, due to the majority of patients have relapsed inevitably and received multiple effective post-relapse treatments [20].…”
Section: Discussionsupporting
confidence: 88%
“…Clinal trial research showed that bortezomib consolidation after ASCT only improved the PFS of patients not achieving at least VGPR, no effect on patients who achieved at least VGPR, and did not prolong OS in both category patients [23]. Consolidation therapy refers to utilize a short course of treatment for reducing the number of residual tumor cells, which cloud prolonged the PFS but not OS [18]. Consolidation and maintenance play a different role in patients' outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Three drug regimens utilising bortezomib, dexamethasone and an additional agent, such as cyclophosphamide (VCd), thalidomide (VTd) or lenalidomide (RVd), are the standard of care prior to autologous stem cell transplantation (ASCT), which utilises a melphalan-based conditioning regimen [ 23 ]. Following ASCT, bortezomib- or lenalidomide-based maintenance therapy is commenced to prolong response, slow progression and improve overall survival [ 24 , 25 , 26 ]. Patients ineligible for an ASCT are still evaluated for induction with bortezomib, lenalidomide or an alkylating-agent based regimen.…”
Section: Standard-of-care Therapy For Multiple Myelomamentioning
confidence: 99%